Performance analysis of periodic gaits in multi-legged locomotion - Tenreiro Machado, J. A. (2019)
This paper presents the kinematic study of periodic gaits for multi-legged locomotion systems. The main purpose is to determine the kinematic characteristics and the system performance during walking. For that objective the precribed motion of the robot is completely characterized in terms of several locomotion variables such as gait, duty factor, body height, step length, stroke pitch, maximum foot clearance, link lengths and cycle time. In this work, we formulate two indices to quantitatively measure the performance of the walking robot namely the perturbation analysis and the locomobility measure. A set of experiments reveal the influence of the locomotion variables in the proposed indices.